Optimizing Local Economic Potential to Increase Regional Food Security through Village-Owned Enterprises Empowerment (Mixed Method: Explanatory Sequential Design) - Rahmat Alhakim; Hakim Hakim; Inam Fakhrul Mujab; Reza Nur Fitriani (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to identify and optimize local economic potential to strengthen regional food security through the empowerment of Village-Owned Enterprises (BUMDes) in Cilacap Regency. Using a mixed-method explanatory sequential design, quantitative analysis was conducted through Klassen Typology, Static and Dynamic Location Quotient (LQ–DLQ) to identify base and prospective agricultural commodities across sub-districts. The results were further elaborated using the Analytic Hierarchy Process (AHP) involving key stakeholders. The findings indicate that rice remains a permanent base commodity, while cassava, soybeans, and sweet potatoes show strong potential for future development. Strategic priorities emphasize food diversification, institutional strengthening of BUMDes, and multi-stakeholder collaboration to support regional food security and the Free Nutritious Meal (MBG) program